SPIRITUAL TRANSFORMATION OF DRUG SURVIVORS THROUGH COMMUNITY-BASED REHABILITATION - Diky Muhamad Fajar; Deddy Mulyana; Susie Purbawasari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the transformative experiences of drug survivors undergoing community-based rehabilitation at Rumah Cemara using Moustakas’ transcendental phenomenological approach. Through in-depth interviews with survivors who had participated in rehabilitation for at least one year and maintained recovery for two years, this research explores the process of reconstructing life meaning, spiritual growth, and the role of community support in addiction recovery. The findings indicate that addiction is a biopsychosocial phenomenon that damages identity and life meaningfulness. Community-based rehabilitation provides a transformative space that enables spiritual metamorphosis, where relapse is interpreted as a learning process rather than a failure. The resulting model of spiritual metamorphosis reflects a complex journey from despair toward the discovery of new meaning and empowerment as agents of social change. The main contribution of this study lies in the development of a holistic, culturally sensitive, and survivor-centered rehabilitation approach, while reinforcing addiction intervention paradigms that emphasize spiritual and social dimensions in Indonesia.